Research of group and chemical composition of pyrocondensate and its products - Запорожець, О.І.; Вовк, О.О.; Нікітченко, Ю.С. (Proceedings of National Aviation University (archive), 2010)
Identity of physical-chemical properties of pyrocondensate with properties of oil-derived products is a reason of erroneous assumption about possible spheres of its application. For example, most spreaded application is like a substitution of heating oil or mazut, but petrol fraction (ab. 30 % of mass) makes this use risky. And some others characteristics don’t correspond to the norms of legacy standards on oil-derived products. That’s why direct using without any technological operations is impossible basing on the technological and ecological safety. Main reason of pyrocondensate incorrect use is connected with insufficient level of investigations and lack of independent and true data of laboratory tests. As far as most laboratory investigations on characteristics and properties of pyro-product are conducted without aim to obtain true information, as real (commercial) goal of similar tests contributes supraliminal limitation and restrict of results, which could be get without any commercial understanding of possibilities of realization. That’s why the receiving of independent results and conclusions is a first-priority task during study of possible spheres of safety and ecological friendly use of pyrocondensate. There were used few methods for laboratory tests, namely: method of accelerated liquid adsorption chromatograph to study a chemical composition of the product, method of infrared and mass-spectrometry to determine a group composition and method of gas fluid chromatograph to investigate a properties of fraction 38°−180° C, obtained at the atmospheric refraction of pyrocondensate. Detailed study of components chemical structure, which are contained in pyro-product, was conducts due to its separation on some narrow fractions by the method of liquid adsorption chromatography. On the base of results of laboratory tests there was established, that without additional chemical treatment and with minimum economics this product, obtained from scrap tires, can be use like a component for production of low-sulfur heating oil, low-viscous watercraft fuel or asphalt mixtures. Since pyro-condensate is a concentrate of olefins- naphthenes-aromatic hydrocarbons (approx. 94%), it can be use as a raw-material for production of high-quality fuels of naphthenes-parafins base. Method of atmospheric rectification allows obtaining a fraction of hydrocarbons with final boiling point 38–180° C (gasoline fraction), but because of high content of unsaturated hydrocarbon use only 10% of this fraction as a component for high-octane fuel. Generically pyrocondensate is a perspective component for substitution of traditional oil products and investigation of its properties is actual task on the way for looking of new sources of alternative energy-carriers.